2018
DOI: 10.1002/jbm.a.36590
|View full text |Cite
|
Sign up to set email alerts
|

Functional bioreactor characterization to assess potentials of nanocomposites based on different alginate types and silver nanoparticles for use as cartilage tissue implants

Abstract: In this work, functional characterization of biomaterials concerning potential application as articular cartilage implants was performed by using a biomimetic bioreactor with dynamic compression in the physiological regime (10% strain, 0.84 Hz frequency, 1 h on/1 h off). Specifically, two alginate types with low (LG) and high (HG) guluronic/mannuronic residue ratios with electrochemically synthesized silver nanoparticles (AgNPs) were evaluated. HG Ag/alginate hydrogels were clearly indicated as potential candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 84 publications
1
3
0
Order By: Relevance
“…Furthermore, these bioreactors can be useful tools also in drug screening, cancer research and characterization of novel biomaterials. As an example, we have previously shown that cytotoxicity studies of Ag/alginate nanocomposite hydrogels in cartilage explant tissue cultures in a biomimetic bioreactor with dynamic compression applied in a regime relevant for articular cartilage have indicated the nanocomposite biocompatibility without signs of cytotoxicity [12]. These results were in accordance with the functionality that these hydrogels exhibited in burn treatments in rats while contrary to moderate cytotoxic effects found in chondrocyte monolayers [12].…”
Section: Introductionsupporting
confidence: 61%
“…Furthermore, these bioreactors can be useful tools also in drug screening, cancer research and characterization of novel biomaterials. As an example, we have previously shown that cytotoxicity studies of Ag/alginate nanocomposite hydrogels in cartilage explant tissue cultures in a biomimetic bioreactor with dynamic compression applied in a regime relevant for articular cartilage have indicated the nanocomposite biocompatibility without signs of cytotoxicity [12]. These results were in accordance with the functionality that these hydrogels exhibited in burn treatments in rats while contrary to moderate cytotoxic effects found in chondrocyte monolayers [12].…”
Section: Introductionsupporting
confidence: 61%
“…For instance, biomimetic bioreactors, which imitate physiological conditions in a certain tissue or organ, are primarily being developed for tissue engineering purposes. Still, these bioreactors also provide physiologically relevant studies of novel biomaterials and interactions of biomaterials with cells and tissues [22][23][24]. Thus, by this approach it is possible to address the in vitroin vivo gap that is, discrepancies between results obtained in traditional monolayer cell cultures (in 2D environment) and those found in animal studies [25][26][27].…”
Section: Research In the Field Of Biomaterials Sciencementioning
confidence: 99%
“…Thus, by this approach it is possible to address the in vitroin vivo gap that is, discrepancies between results obtained in traditional monolayer cell cultures (in 2D environment) and those found in animal studies [25][26][27]. It was shown, for example, that nanocomposite alginate hydrogels with AgNPs had moderate to strong cytotoxic effects on chondrocytes in monolayers, while such effects were entirely absent in 3D bioreactor cultures of immobilized chondrocytes in alginate microbeads as well as in cartilage tissue cultures in a direct contact with the nanocomposite hydrogel [23,28]. The results obtained in the bioreactor cultures were in agreement with the enhancement of wound healing without any adverse effects found in the treatment of 2 nd degree burns in rats by the same nanocomposite hydrogels [21].…”
Section: Research In the Field Of Biomaterials Sciencementioning
confidence: 99%
“…The size distribution of electrochemically synthesized (galvanostatic method) AgNPs in Ag/Alg colloid solutions and hydrogels was evaluated by TEM imaging and the distribution was found to be fairly narrow for colloids and hydrogels based on low-viscosity alginate, in the 3 to 18 nm range, with average values around 8 to 9 nm. 140 On the other hand, medium-viscosity alginate hydrogels and colloids contained a broader AgNPs size distribution (3-28 nm), with larger average particle diameters (9-12 nm), 140 indicating that the choice and properties of the polymer matrix play an important role in controlling the AgNPs characteristics. Similar results were obtained for chitosan-containing hydrogels, which were analyzed by DLS as also discussed above.…”
Section: Polymer-based Wound Dressings With Electrochemically Incorporated Silver Nanoparticles and Their Propertiesmentioning
confidence: 99%